The Effect of Online Transactions (E-Commerce) with the COD Payment System on the Income Guarantee of Culinary MSME in Mataram City - Ramadhani, Dimas; Jumaidi, Lalu Takdir (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research was conducted in West Nusa Tenggara Province, more precisely in Mataram City. The purpose of this study is to analyze how influential the use of online transactions (e-commerce) with the Cash on delivery (Cod) payment system on the income guarantee of culinary MSMEs in Mataram City. The research method used is quantitative research. This study uses primary data obtained through the distribution of questionnaires to respondents and has obtained a sample of 43 people (business actors). The estimation method used is multiple linear. The results show that the variables of E-commerce and Cash on delivery have an effect on the income of culinary micro, small and medium businesses in the city of Mataram. partially, the e-commerce and Cash on delivery variables have a positive and significant effect on the income of MSMEs in the city of Mataram.